Integrating Ground LiDAR Scanning Techniques for Structural Mapping in an Active Marble Quarry - Vassilakis, Emm; Stavropoulou, M.; Konsolaki, A.; Exadaktylos, G. (Mediterranean Geosciences Union, 5th Annual Meeting, 2025)
Understanding the subsurface structural framework of mines is critical for ensuring operational safety. Especially in room and pillar marble quarries, where extraction strategies need continuous optimization and reorientation and since benching creates rooms with considerable heights, ensuring structural stability is crucial for the safety of personnel and equipment. This study presents a novel application of ground-based Li-DAR (Light Detection and Ranging) technology for high-resolution structural mapping within an active marble quarry. By deploying terrestrial laser scanning across key excavation galleries, we generated detailed 3D point clouds that reveal hidden discontinuities and fault systems with a non-invasive, rapid, and precise methodology, capable for representing de-tailed three-dimensional models of the quarry interiors. We used a Leica P50 scanner for acquiring point data in this marble quarry, covering an area of 8,800 m2. A volume of 46,900 m3 was mapped in high detail by setting up 9 bases, accompanied with the measurement of 12 ground control points (GCPs), which were utilized for the transform of al-most 960 million points into real coordinates.The resulting point cloud data were processed using ad-vanced geospatial software to generate 3D models and ex-tract structural features such as joints, faults, bedding planes, and correlate them with existing geological models, which were derived from classical surface mapping of outcrops. The analysis revealed several previously undocumented sub-surface structures that have direct implications for resource estimation, selection of support measures and operational planning. The high spatial resolution of LiDAR enabled the identification of subtle features that are typically missed by conventional surveying techniques.This study demonstrates that ground-based LiDAR is a pow-erful tool for subsurface structural mapping in marble quar-rying, offering significant advantages in terms of accuracy, safety, and efficiency.